Valenţe ale implicării civice în mediul liceal - Drăghici, Elisaveta (Calitatea Vieții, 2017)
The topic of civic participation of young people (especially those who do not yet have the ability to express by vote and who are still attending high school) is of real interest to any society. This research reveals the young people's vision of civic education and civic involvement, focusing on identifying civic education topics of interest to students, identifying civic engagement methods agreed by students, and exploring the perception of setting up a civic engagement club in high schools to practice civic conduct skills. The study found that as young people receive a minimum of information about civic education, they become receptive to what is happening around them. They are concerned with topics such as tolerance in society, attitudes to controversial public issues, civil society, civic organizations, election of representatives, and the exercise of rights and responsibilities in a democratic society. At the same time, young people's preferences were identified, focusing on their attraction by public debates, classroom/ outside classroom exercises and simulations, lobbying and relief actions. Consequently, young people accept the idea of setting up a civic education club in school and recognize the importance in their development as citizens with rights and responsibilities, and would be willing to engage in different actions to develop civic sense.